Familial mental retardation in a family with an inherited chromosome rearrangement. Issue 4 (December 1974) - Chudley, A. E.; Bauder, F.; Ray, M.; McAlpine, Phyllis J.; Pena, S. D. J.; Hamerton, J. L.
Abstract : A family of three generations has been described with an insertional type of chromosome rearrangement involving chromosomes 11 and 18[46, XX or XY, ins(11;18)(p15;q11q21)] detected by G-banding using a trypsin digestion method. Four members of this family with clinical features of 18q− have inherited the der(18) from their father and are thus deficient for (18)(q11q21). Three other family members have inherited the der(11) and thus have a duplication of the same segment [(18)(q11q21)]. Genetic marker studies on this family, show no significant segregation of any of the markers studied with either the der(11) or der(18). Eight family members had the PepA 8 PepA 1 genotype and four of these were carrying the der(18), indicating that the PepA locus which had been previously assigned to chromosome 18, does not lie in the segment q11→q21.